Retrieval of proximally migrated double J ureteric stents in children using goose neck snare - Sivasankar Jayakumar; Mohamed Marjan; Key Wong; Amman Bolia; George K Ninan (Wolters Kluwer Medknow Publications, 2012)
Purpose: Proximal migration of the ureteric double J stent is a rare but known complication. We describe three cases where a minimally invasive technique for retrieval of displaced double J stents using Amplatz™ goose-neck snare was successful. Materials and Methods: A retrospective review of patients with displaced double J stent was carried out, in whom cystoscopy guided retrieval of double J stent was attempted with the help of Amplatz goose-neck snare under radiological control. Results: All three patients were under the age of 3 years. Two patients had migrated double J stent following pyeloplasty and in one patient the double J stent was displaced during a retrograde insertion of double J stent. In all cases, retrieval of displaced double J stent was successfully achieved using Amplatz goose-neck snare. There were no postoperative complications. Conclusion: Our method of retrieval of stent from renal pelvis is simple, safe and minimally invasive. This technique is a useful and safe alternative option for retrieval of proximally migrated double J stents in children.